An empirical study of e-commerce applied by Bustead Information Technology Sdn. Bhd. / Ros Dalia Kahadin - Kahadin, Ros Dalia (2010)
This case study was conducted to determine the best marketing and promotional tools that can be applied on to the BIT-e portal. For the Chapter 1 explains the background and the introduction of the research. Chapter 2 is explaining the literature review to support the research, while Chapter 3 explores the research methodology and the sampling technique. In Chapter 4 will discuss the finding and the last chapter is Chapter 5 will share the conclusion and the recommendation towards the finding. The finding shows that BIT-e is more focused on offline marketing rather than online marketing even though there had put e-commerce activity in the company's websites. Based on the finding, some recommendations have been suggested in order to help Boustead Information Technology Sdn. Bhd improved the marketing activities via online and also will enhance their service performance to increase profit.